2012
DOI: 10.1097/bpb.0b013e3283536962
|View full text |Cite
|
Sign up to set email alerts
|

Congenital trigger thumb in children

Abstract: Although numerous studies have been performed on congenital trigger thumb (CTT), the pathogenesis is still unknown. Cytocontractile proteins and myofibroblasts are present during soft-tissue contraction, and they may have a role in CTT. The aim of the study is to clarify the immunohistochemical and the electron microscopy characteristics of the first annular (A-1) pulley in CTT. The specimens from the A-1 pulleys were collected from 22 children with CTT. Electron microscopy was used to study the last five spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 26 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Paediatric trigger thumb was previously thought to be a congenital condition with several studies having reported pathological changes to the A1 pulley or FPL tendon. Some authors (Buchman et al., 1999; Khoshhal et al., 2012) found that patients with paediatric trigger thumb have pathologic fibrous tissue in and around the FPL tendon and A1 pulley, including proliferation of fibroblasts and surrounding collagen. However, a number of neonatal surveys (Kikuchi and Ogino, 2006; Moon et al., 2001; Rodgers and Waters, 1994) failed to demonstrate a convincing incidence of paediatric trigger thumb at birth, indicating this is more likely to be an acquired condition.…”
Section: Discussionmentioning
confidence: 99%
“…Paediatric trigger thumb was previously thought to be a congenital condition with several studies having reported pathological changes to the A1 pulley or FPL tendon. Some authors (Buchman et al., 1999; Khoshhal et al., 2012) found that patients with paediatric trigger thumb have pathologic fibrous tissue in and around the FPL tendon and A1 pulley, including proliferation of fibroblasts and surrounding collagen. However, a number of neonatal surveys (Kikuchi and Ogino, 2006; Moon et al., 2001; Rodgers and Waters, 1994) failed to demonstrate a convincing incidence of paediatric trigger thumb at birth, indicating this is more likely to be an acquired condition.…”
Section: Discussionmentioning
confidence: 99%
“…13 While ultrasound has identified a larger-than-normal size of FPL compared with the contralateral uninvolved FPL tendon, both ultrasound and electron microscopy of the flexor tendon have not demonstrated inflammatory or degenerative changes of the tendon. 14 15 16…”
Section: Pediatric Trigger Thumbmentioning
confidence: 99%
“…13 While ultrasound has identified a larger-than-normal size of FPL compared with the contralateral uninvolved FPL tendon, both ultrasound and electron microscopy of the flexor tendon have not demonstrated inflammatory or degenerative changes of the tendon. [14][15][16] The most common classification system used is that of Sugimoto, in which stages range from a palpable Notta's nodule without triggering of the thumb to a locked IP joint without active or passive extension (►Table 1). 17 Pediatric trigger thumb is diagnosed based on physical exam with no need for imaging.…”
Section: Pediatric Trigger Thumbmentioning
confidence: 99%
“…Fahey and Bollinger found collagenous degeneration and synovial proliferative changes within the flexor tendon [11] . More recently, both ultrasound and electron microscopy of the flexor tendon have not demonstrated inflammatory or degenerative changes [15,16] . Electron microscopy identified cytocontractile proteins and myofibroblasts within the tendon, further suggesting a developmental process [16] .…”
Section: Etiologymentioning
confidence: 99%